Effect of acute heat stress on intestinal immune response of Jinding ducks - Xiaopan Liu; Li Li; Zhongwei Miao; Qingwu Xin; Linli Zhang; Qiannan Cai; Wenli Shi; Bangzhe Zhao; Nenzhu Zheng; Zhiming Zhu (Poultry Science)
Heat stress (HS) is a critical factor affecting the health and performance of poultry. This study investigated the effects of varying durations of HS on antioxidant capacity and intestinal damage in Jinding ducks. The ducks were exposed to an environment at 40°C for 1 h, 3 h, 6 h, and 12 h to simulate HS conditions. The impact of HS on intestinal health was assessed by measuring the expression of small intestinal heat shock proteins, inflammatory factors, intestinal digestive enzyme activity, intestinal permeability, and pathomorphological changes in the jejunum. The results showed that with prolonged HS, the expression of antioxidant capacity and heat shock proteins initially increased and then decreased, while intestinal inflammation and damage progressively intensified. Notably, after 12 h of HS, there was a significant increase in intestinal permeability, impaired barrier function, decreased digestive enzyme activity, pronounced disturbances in jejunal morphology, and a substantial reduction in immune cell numbers. These findings suggest that Jinding ducks subjected to 12 h of HS at 40°C can serve as a model for acute HS. This study not only elucidated the alterations in antioxidant and intestinal immunity in Jinding ducks associated with extended HS but also provided a scientifically robust experimental model for future research on anti-HS agents. The results were significant for a deeper understanding of the mechanisms through which HS affects poultry health and offered a scientific basis for developing new strategies to mitigate HS impacts.